pH-Triggered Adhesiveness and Cohesiveness of Chondroitin Sulfate-Catechol Biopolymer for Biomedical Applications - Scalzone, Annachiara; Bonifacio, Maria A.; Cometa, Stefania; Cucinotta, Fabio; De Giglio, Elvira; Ferreira, Ana M.; Gentile, Piergiorgio (Frontiers in Bioengineering and Biotechnology, 2020)
Nature provides biomaterials that tend to be effective to control both their adhesive and cohesive properties. A catecholamine motif found in the marine mussels, the mytilus edulis foot protein, can play adhesiveness and cohesiveness. Particularly, acidic pH drives catechol to have adhesive function, resulting in surface coating, while basic pH allows to enhance its cohesive properties, resulting in the formation of hydrogels. In this work, we demonstrated the usefulness of catechol (Cat)-conjugated chondroitin sulphate (CS) as a platform for mesenchymal stem cell culture, utilizing the adhesive property of CS-Cat as coating for different substrates and the cohesive properties as hydrogel for cells encapsulation. To prepare the CS-Cat biopolymer, dopamine was coupled to the CS by carbodiimide coupling reaction and the catechol content was determined by UV-Vis spectroscopy (4.8±0.6%). To demonstrate the adhesive properties of the biopolymer, PLA, PCL, TiO2 and SiO2 substrates were immersed in CS-Cat solution (pH<2). Following the coating, the surfaces became highly hydrophilic, exhibiting a contact angle less than 35°. Also, in the presence of an oxidizing agent at pH 8, CS-Cat solution immediately became a hydrogel, as shown by inverted-vial test. Finally, immortalised TERT human mesenchymal stem cells (Y201) confirmed the high cytocompatibility of the biopolymer. The CS-Cat coating significantly enabled the Y201 adhesion onto PLA substrates, while the prepared hydrogel demonstrated to be a suitable environment for the encapsulation of cells as suitable bioink for further bioprinting applications.